2021
DOI: 10.1038/s41598-021-85672-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small and highly dispersive iron oxide hydroxide as an efficient catalyst for oxidation reactions: a Swiss-army-knife catalyst

Abstract: Ultra-small and highly dispersive (< 10 nm) iron oxide hydroxide is characterized by some methods. The compound is an efficient and stable catalyst for alcohol oxidation, organic sulfide oxidation, and epoxidation of alkenes in the presence of H2O2. The electrochemical oxygen-evolution reaction of the iron oxide hydroxide is also tested under acidic, neutral, and alkaline conditions. In the presence of the iron oxide hydroxide, excellent conversions (75–100%) and selectivities of substrates (92–97%), depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 50 publications
3
14
0
1
Order By: Relevance
“…Post‐XRD analysis demonstrates that the generation of new active phases occur exclusively on the surface of the rCoFe‐PBA/NF, rather than throughout the catalyst. The post‐IR spectra of rCoFe‐PBA/NF (Figure S7) shows new peaks at 890 cm −1 (M−OOH), 1356 cm −1 (H 2 O‐bending) and 1635 cm −1 and 3000–3500 cm −1 corresponds to −OH [68–73,36] . The post‐IR spectrum analysis implying a phase transition from rCoFe‐PBA/NF to oxyhydroxides formation which is in agreement with post‐XRD results.…”
Section: Activity and Stability Of Rcofe‐pbasupporting
confidence: 85%
See 2 more Smart Citations
“…Post‐XRD analysis demonstrates that the generation of new active phases occur exclusively on the surface of the rCoFe‐PBA/NF, rather than throughout the catalyst. The post‐IR spectra of rCoFe‐PBA/NF (Figure S7) shows new peaks at 890 cm −1 (M−OOH), 1356 cm −1 (H 2 O‐bending) and 1635 cm −1 and 3000–3500 cm −1 corresponds to −OH [68–73,36] . The post‐IR spectrum analysis implying a phase transition from rCoFe‐PBA/NF to oxyhydroxides formation which is in agreement with post‐XRD results.…”
Section: Activity and Stability Of Rcofe‐pbasupporting
confidence: 85%
“…45‐0031) [75] . The post‐IR spectra (Figure S11) of rCoFe‐PBA/NF shows new peaks at 890 cm −1 (M−OH), 1356 cm −1 (H 2 O‐bending) and 1635 cm −1 and 3000–3500 cm −1 corresponds to −OH [68–73,36] . The post‐IR spectrum analysis implying transition from rCoFe‐PBA/NF to metal and metal hydroxides formation which is in agreement with post‐XRD results.…”
Section: Activity and Stability Of Rcofe‐pbasupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, in the case of Mn-doped cerium oxide catalysts, the reaction conditions involve high energy consumption. Until now, iron oxide hydroxide (FeOOH) was used as an efficient catalyst only for alcohol oxidation, organic sulfide oxidation, and epoxidation of alkenes in the presence of H 2 O 2 73 while the catalytic activity of FeOOH based nanocomposites containing MnO(OH), Co(OH) 2 , Ni(OH) 2 , CuO or ZnO in the epoxidation of cyclooctene with molecular oxygen has not been reported. Such catalytic systems could present interest since their synthesis is not difficult and does not imply high costs.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46] On the other hand, the iron-based catalysts advantages are their reaction intermediates, Fe-hydroxides/ oxides, that can serve as the active species for catalytic reactions. 47,48 Recent studies have shown that transition metal doping such as Fe, Co, and Ni alters the electronic structure and improves the conductivity and electrochemical properties of MoS 2 . [49][50][51][52][53][54][55][56][57] However, only a few works were reported on transition metals incorporated MoS 2 for the OER activity.…”
Section: Introductionmentioning
confidence: 99%